Tryptophan biosynthesis in stramenopiles: eukaryotic winners in the diatom complex chloroplast - Jiroutová, Katerina; Horák, Ales; Bowler, Chris; Oborník, Miroslav (Journal of molecular evolution, 2007)
Tryptophan is an essential amino acid that, in eukaryotes, is synthesized either in the plastids of photoautotrophs or in the cytosol of fungi and oomycetes. Here we present an in silico analysis of the tryptophan biosynthetic pathway in stramenopiles, based on analysis of the genomes of the oomycetes Phytophthora sojae and P. ramorum and the diatoms Thalassiosira pseudonana and Phaeodactylum tricornutum. Although the complete pathway is putatively located in the complex chloroplast of diatoms, only one of the involved enzymes, indole-3-glycerol phosphate synthase (InGPS), displays a possible cyanobacterial origin. On the other hand, in P. tricornutum this gene is fused with the cyanobacteria-derived hypothetical protein COG4398. Anthranilate synthase is also fused in diatoms. This fusion gene is almost certainly of bacterial origin, although the particular source of the gene cannot be resolved. All other diatom enzymes originate from the nucleus of the primary host (red alga) or secondary host (ancestor of chromalveolates). The entire pathway is of eukaryotic origin and cytosolic localization in oomycetes; however, one of the enzymes, anthranilate phosphoribosyl transferase, was likely transferred to the oomycete nucleus from the red algal nucleus during secondary endosymbiosis. This suggests possible retention of the complex plastid in the ancestor of stramenopiles and later loss of this organelle in oomycetes.
Keywords: sekvence aminokyselin; Phytophthora; Chloroplasts; tryptofansynthasa; Evolution, Molecular; Indole-3-Glycerol-Phosphate Synthase; tryptofan; molekulární struktura; aldosa-ketosaisomerasy; fylogeneze; indol-3-glycerolfosfátsynthasa; Molecular Structure; anthranilátsynthasa; rozsivky; anthranilátfosforibosyltransferasa; Aldose-Ketose Isomerases; Anthranilate Phosphoribosyltransferase; molekulární sekvence - údaje; chloroplasty; Molecular Sequence Data; Tryptophan Synthase; Anthranilate Synthase; Diatoms; Phylogeny; Amino Acid Sequence; molekulární evoluce; Tryptophan